Study the vegetative growth and yield of some grapes varieties (Vitis vinifera L.) - Faraidun Karim Ahmad; Shayan Akram Mustafa; Zainab Sabah Lazm; Shawkat Mustafa Mohammed Al-Atrushy (Kufa Journal for Agricultural Sciences)
This study was carried out in Sulaimani governmental during 2018 growing season to study the vegetative growth and yield characteristic of seven cultivars of grapevine. The seven the vines were trained by bilateral horizontal cordon on T-Trellis system. Therefore, the experiment consisted of seven treatments with three replications; one individual vine for each experimental unites and applied as simple experiment by using (RCBD) design, so the numbers of vines used were 21 vines. Results indicated that Bedank cultivar superior other cultivars in term of leaf area, total chlorophyll, leaf fresh and dry weight, Petiole length, Inter nod length and shoot length. According to yield characteristics Des Alannz and Sadane gave the highest cluster wide and cluster length, Bedank cultivar gave the highest cluster weight and Number of berry/ cluster. Mirane cultivar significantly superior other cultivars regarding the size and weight of 100 berries, berry diameter, weight of 100 seed. Concerning the chemical characteristics of grape Mirane cultivar where registered the highest total sugar percent, total soluble solids and juice density, Bedank gave the highest juice percentage, results illustrate that total acidity was the lowest at Rumaiabiaz.